2021
DOI: 10.1080/14992027.2020.1853263
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging the age friendly healthcare system initiative to achieve comprehensive, hearing healthcare across the spectrum of healthcare settings: an interprofessional perspective

Abstract: Objective: Hearing loss is associated with multiple physical, cognitive, and psychosocial co-morbidities. Achievement of safe healthcare in the context of these complex co-morbidities necessitates accurate hearing and coordination across specialties. This paper discusses the potentials for and barriers to an interprofessional approach to integrating hearing screening and treatment across all healthcare settings. Design: The paper reviews the relationship between hearing loss and other health care concerns to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 55 publications
(47 reference statements)
1
15
0
Order By: Relevance
“…However, no between-group differences were found in the types of chemotherapy regimens or doses of neurotoxic chemotherapy. The positive association between hearing loss and a higher comorbidity burden is consistent with studies in the general population [ 47 ].…”
Section: Discussionsupporting
confidence: 89%
“…However, no between-group differences were found in the types of chemotherapy regimens or doses of neurotoxic chemotherapy. The positive association between hearing loss and a higher comorbidity burden is consistent with studies in the general population [ 47 ].…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, there is little risk that interventions targeting cardiovascular disease would exacerbate hearing problems. As such, there have been increasing calls for hearing healthcare to take a more interdisciplinary and holistic approach, as well as to address the broader health needs of individuals with hearing loss to promote overall health and well-being [ 36 , 37 ].…”
Section: Associations Between Hearing and Healthmentioning
confidence: 99%
“…2 Furthermore, as noted earlier, it may be especially valuable to develop interprofessional approaches and multidimensional interventions that target the range of factors that affect hearing or are associated with hearing loss. 3 The findings of the study by Martinez-Amezcua et al 1 support the need for continued research designed to further tease apart the mechanisms underlying the association of hearing loss with health outcomes, including with poor physical function. Additionally, intervention studies aimed at improving hearing or mitigating hearing loss are needed to fully understand whether such correction affects health outcomes.…”
mentioning
confidence: 93%
“…2 Hearing health research has focused on these consequences as well as on the intriguing association of hearing impairment with cognitive functioning and dementia. 2,3 Physical health outcomes have been less commonly addressed in connection to hearing loss, especially in contrast to visual impairments. However, prior work has established hearing loss as a potential risk factor for falls, 4,5 and a few studies have found associations with physical activity and overall measures of physical functioning.…”
mentioning
confidence: 99%